2008
DOI: 10.1016/j.foodhyd.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular flexibility of citrus pectins by combined sedimentation and viscosity analysis

Abstract: The flexibility/ rigidity of pectins plays an important part in their structure -function relationship and therefore on their commercial applications in the food and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 39 publications
7
45
0
1
Order By: Relevance
“…The intrinsic viscosities of both pectins (Tables 1 and 2) after preparation (t = 0) are in good agreement with previous measurements [15] and are consistent with other studies on citrus pectins [17][18][19][20][21][22].…”
Section: Intrinsic Viscosities and Gel Strengths Of Pectinssupporting
confidence: 92%
See 3 more Smart Citations
“…The intrinsic viscosities of both pectins (Tables 1 and 2) after preparation (t = 0) are in good agreement with previous measurements [15] and are consistent with other studies on citrus pectins [17][18][19][20][21][22].…”
Section: Intrinsic Viscosities and Gel Strengths Of Pectinssupporting
confidence: 92%
“…The pectins also formed gels of similar strength in terms of area under the force-time curve (AUC) (Tables 1 and 2); this is consistent with their solution properties [15].…”
Section: Intrinsic Viscosities and Gel Strengths Of Pectinssupporting
confidence: 75%
See 2 more Smart Citations
“…These biopolymers serve as wall materials with desirable properties such as a good solubility, but they differ in interfacial functionality and rheological properties (Fortuna et al 2004;Weinbreck & Wientjes 2004;Norziah et al 2006). Their flexibility or rigidity also play an important role in their structure-function relationship and in commercial applications in the food and biomedical industries (Morrisa et al 2008). Most notably, Pedroza-Islas et al (1999) reported that particle size and microcapsule microstructure varied with the biopolymers selected as wall materials.…”
mentioning
confidence: 99%